Dispositivo microfluídico de borracha natural (LAB-ON-A-CHIP) - Cabrera, Flávio Camargo [UNESP] (2015)
This thesis reports a new concept of flexible microfluidic device, using natural rubber as alternative material, flexible and stretchable, for based-plataforms of lab-on-a-chip-devices. The device preparation is carried out dropping the latex over the mold, supported on acrylic dishes, containing the configuration of the device. The latex should cover the entire structure by casting method and, subsequentely subjecting it to thermal treatment to form the natural rubber membranes. The membranes demolded should replicate the configuration of the device on its surface. Poly(vinyl chloride) (PVC) films are implement as covering layer on internal surface, avoiding thw water absorption e protein compounds leaching from natural rubber membranes. The flexible devices of natural rubber were implemented as optical and electrochemical sensors, using flexible carbon fibers as electrodes internal electrodes. Becomes important emphasize, that the natural rubber membranes are transparent when considering the visible region in the electromagnetic sprectrum as well as it is biocompatible, allowing the combination of mechanical, optical and biological properties in a single device. Rely on electrochemical analysis devices demonstrate good stability and resistance for long term stability maintaining the characteristic curve of potential as well as a short interval of time necessary to reach the stationary current for each electrochemical process. In a second instance, we used the natural rubber-based microfluidic as microreactor for the synthesis of magnetic nanoparticles (Fe3O4) decorated with gold nanoparticles (Fe3O4-AuNPs). The synthesis of decorated nanoparticles (Fe3O4-AuNPs) shows effectiveness in order to obtain high degree of homogeneity on gold nanoparticles distribution over the surface of magnetite particles, reaching averages sizes of 6.3 nm